Rating the Quality of Open Textbooks: How Reviewer and Text Characteristics Predict Ratings - Fischer, Lane; Ernst, David; Mason, Stacie L (International Review of Research in Open and Distributed Learning, 2017)
Using data collected from peer reviews for Open Textbook Library titles, this paper explores questions about rating the quality of open textbooks. The five research questions addressed the relationship between textbook and reviewer characteristics and ratings. Although reviewers gave textbooks high ratings generally, reviewers identified differences in quality according to criteria and discipline. Physics and chemistry textbooks earned significantly lower ratings than other textbook types. Ratings were not significantly associated with reviewers’ status and experience, but were associated with reviewers’ place of residence. We discuss the implications for OER efficacy studies and other research.